IMPROVEMENT OF TRAFFIC ORGANIZATION IN PEDESTRIAN CROSSINGS - D. V. Kapsky (Наука и техника)
The paper provides aspects of pedestrian traffic organization in the case when pedestrians cross roadway (street). Some negative points concerning pedestrian-vehicle right transfer for starting movement are revealed in the paper. The paper gives recommendations for elimination of these disadvantages.